Interconnecting the network of networks - Noam, Eli M. (MIT Press, 2001)
This book describes the transformation of telecommunications from national network monopolies to a new system, the "network of networks," and the glue that holds it together, interconnection. By their very nature, monopoly-owned networks provided a small number of standardized, nationwide services. Over the past two decades, however, new forces in the world economy began to unravel this traditional system. The driving force behind the change was the shift toward an information-based economy. Especially for large organizations, the price, control, security, and reliability of telecommunications became variables requiring organized attention. Thus, monopoly began to give way to the "network of networks," the foundation of today's telecommunications and Internet infrastructure. Taking a broad, multidisciplinary perspective Eli Noam discusses the importance and history of interconnection policy, as well as recent policy reforms both within the United States and around the globe. Other important topics he discusses include interconnection prices, the unbundling of interconnection, and the technology of interconnection. He concludes with an examination of social and policy issues, including the free flow of content, universal service and privacy protection, and the future of telecommunications